2021
DOI: 10.3390/jcm10040666
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Diagnostic Criteria for Gestational Diabetes Mellitus on Adverse Maternal Outcomes: A Systematic Review and Meta-Analysis

Abstract: This systematic review and meta-analysis aimed to examine the impact of different gestational-diabetes (GDM) diagnostic-criteria on the risk of adverse-maternal-outcomes. The search process encompassed PubMed (Medline), Scopus, and Web of Science databases to retrieve original, population-based studies with the universal GDM screening approach, published in English language and with a focus on adverse-maternal-outcomes up to January 2020. According to GDM diagnostic criteria, the studies were classified into s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 82 publications
(162 reference statements)
2
19
0
Order By: Relevance
“…To the best of our knowledge, exercise therapy is exercise program tailored based on the patient's conditions to help them control their blood sugar [ 17 , 18 ]. Previous research has demonstrated that insulin combined with individualized exercise gains promising results in the treatment of gestational diabetes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, exercise therapy is exercise program tailored based on the patient's conditions to help them control their blood sugar [ 17 , 18 ]. Previous research has demonstrated that insulin combined with individualized exercise gains promising results in the treatment of gestational diabetes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…We did not have information regarding the potential impact of the different glucose tolerance classifications on neonatal outcomes, which is a major limitation of our study. However, a recent systematic review and meta-analysis showed that the increased risk of maternal outcomes (i.e., primary cesarean, induction of labor, maternal hemorrhage, and pregnancy-related hypertension) of women with GDM compared with women without GDM was not influenced by the GDM diagnostic classification [21]. A second limitation is the lack of information on pregnant women from follow-ups after the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It is defined as a glucose tolerance disorder that develops or is first recognized during pregnancy [ 57 ]. The recommended diagnostic criteria are based on the presence of at least one of the threshold values during the 75 g-oral glucose tolerance test (75g-OGTT): fasting glucose level of 5.1–6.9 mmol/L (92–125 mg/dL) at the first hour ≥ 10.0 mmol/L (≥180 mg/dL) and at the second hour 8.5–11.0 mmol/L (153–199 mg/dL) [ 58 ]. Epidemiological studies have revealed that a previous history of impaired glucose tolerance, personal history of medical conditions associated with diabetes (e.g., metabolic syndrome, polycystic ovary syndrome, glucocorticoids use), overweight or obesity, advanced maternal age, dyslipidemia, and history of poor pregnancy outcome or macrosomia in a previous pregnancy seem to be the pivotal risk factors for GDM development [ 59 , 60 ].…”
Section: Role Of Kisspeptin In Gestational Diabetes Mellitus—a Placen...mentioning
confidence: 99%